Year-long Concurrent MAX-DOAS Observations of Nitrogen Dioxide and Formaldehyde at Pune: Understanding Diurnal and Seasonal Variation Drivers - Mriganka Sekhar Biswas; Anoop S. Mahajan (Aerosol and Air Quality Research)
Abstract Year-long observations of nitrogen dioxide (NO2) and formaldehyde (HCHO) using the Multi-Axis Differential Absorption Spectroscopy (MAX-DOAS) technique are reported from Pune City, India. We studied the diurnal and seasonal variations, effect of biomass burning and the weekend effect on both species. NO2 diurnal profiles displayed a traffic induced peak at ~09:00 hrs. HCHO also showed a morning peak ~10:00 hrs due to production from oxidation of VOCs in the presence of solar radiation. Both NO2 and HCHO show the highest average concentrations during the winter (October, November, December, January and February—ONDJF), with mean mixing ratios of 2.0 ± 1.4 ppb and 3.0 ± 1.4 ppb, respectively. These observations suggest that a lower boundary layer (BL) height during ONDJF leads to higher concentrations of trace gases. During June, July, August, and September (JJAS), both trace gases show a minimum in their concentrations, with average mixing ratios for NO2 and HCHO being 0.9 ± 0.6 ppb and 1.1 ± 0.7 ppb, most likely due to removal by wet deposition. There was no significant difference in both the trace gases on weekdays and weekends. Using back-trajectory analysis, we conclude that air parcels coming from regions of biomass burning increased the concentrations in Pune. Emissions from nearby industrial areas of Bhosari and Pimpri-Chinchwad increased NO2 concentrations in Pune city. Finally, we compared the observations with previous reports over India and found that both HCHO and NO2 concentrations are lower in Pune compared to the other large cities in India.